Fruit Morphological Characteristics and Î²-carotene Content of Three Indonesian Dessert and Cooking Banana Cultivars - Ari Sunandar; Dedeh Kurniasih (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Approximately, 325 cultivars of bananas were found in Indonesia. They have variation in shape, taste, color of fruit pulp, essential vitamins and mineral. The Î²-carotene is one of essential nutrient in banana with various concentration in every cultivar. The aims of this research were to describe the morphological characteristics and to analyze Î²-carotene content of mature fruits of three different genomic groups of Indonesian dessert and cooking banana cultivars namely Berlin (AA/dessert), Barangan (AAA/dessert), and Kepok (ABB/cooking). Morphological characterizations of fruits were conducted according to Descriptor for Banana from International Plant Genetic Resources Institute. The Î²-carotene content of mature banana pulp was analyzed using High-performance liquid chromatography (HPLC) method with three replications. Banana fruit characters were analyzed based on 15 descriptors. The bananas were then subjected to clustering analysis. Â The result showed that Î²-carotene contentÂ were 27 Î¼g 100g-1, 5 Âµg 100g-1, and 3 Î¼g 100g-1 fresh weight respectively. Berlin showed the highest value of Î²-carotene. Cluster analyses formed two groups. The first group consists of Berlin and Barangan while the second one consists of Kepok. This study can be used as a a reference for people to consume bananas with high content of Î²-carotene in meeting the needs of vitamin A and as a consideration for the plant breeding especially for Î²-carotene improvement purpose.